Analisis Rokat Tase’ di Kalangan Masyarakat Kepulauan Giligenting dan Talango Sumenep Madura - frdus (JURNAL ILMU AL-QUR'AN DAN TAFSIR NURUL ISLAM SUMENEP, 2024)
Religion is a determinant for its adherents. Meanwhile, noble values that are rooted in a tradition certainly have spiritual- mystical, socio-religious energy which is believed to strengthen ties of love between people and bring us closer to God. The Giligenting and Talango islands have marine tourism objects and this religious tourism has the Rokat Tase’ tradition which has values, norms, ethics, customs and customary laws that are upheld by the local community. Resident who in fact work as fishermen, every year organize and interpret it as local wisdom, because this tradition gives direction to cultural development and answers the pros and cons of the rokat tase’ law in a religious context. Therefore, qualitative field research is socio-culturally based and uses an ethnographic approach to reveal, explore and substantially develop data about the reality of certain cultures and traditions. To obtain accurate data, interviews, observation and documentation were used. The results of this research conclude that the two traditions have differences. The difference is that Giligenting no longer uses jittek and replaces it with religious activities. This tradition is carried out using cash from members of the savings and loan arisan. While in Talango they still use releasing offerings, people’s entertainment and collaboration with the village government. This tradition is held as an expression of gratitude for the abundance of good fortune given by Allah. This tradition teaches future generations not to be greedy for nature, to protect marine ecosystems, and to minimize conflicts between people. With the spirit of mutual cooperation, this tradition is successfully held every year. It’s just that in the Talango, rokat tase’ it is no longer held because residents have changed professions as grocery store traders in Jakarta. Keyword: Mark, Rokat Tase’, Public